Development Optimal Strategies for Media Policy of IRIB on Issue of Climate Change - Sarabi, Said (Modern applied science, 2016)
The main objective of this research is developing optimal strategy for IRIB in relation to climate change. Arising Threats from climate change for human life and other creatures resulted in different media productions, all around the world. It is needed for IRIB to pay more attention to climate change problem in its programs, far more than current talk shows with experts. Achieving this goal with no strategy seems impossible. In order to develop an optimal strategy for IRIB in relation to climate change, with the use of "in-depth interview" method, researcher provided the needed information from a couple of interviews with environment experts. With the use of in depth interviews, at first, current situation of climate change topic in IRIB, and then the responsibility of IRIB in relation to climate change were discussed. The next step was finding required information about climate change for a typical audience; this information is extracted from interviews with climatology and environment experts. Using internal and external factors' analysis on IRIB performance on climate change, IRIB strengths, and weaknesses on subject and external threats and opportunities for IRIB in climate change topic were specified, and by the use of SWOT analysis all possible strategies were found. Finally the researcher found that optimal strategy for IRIB is an aggressive strategy.